2008
DOI: 10.5012/bkcs.2008.29.2.413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Carbons with Controllable N-Content and Their Supercapacitor Properties

Abstract: A synthesis route to ordered mesoporous carbons with controllable nitrogen content has been developed for high-performance EDLC electrodes. Nitrogen-doped ordered mesoporous carbons (denoted as NMC) were prepared by carbonizing a mixture of two different carbon sources within the mesoporous silica designated by KIT-6. Furfuryl alcohol was used as a primary carbon precursor, and melamine as a nitrogen dopant. This synthesis procedure gave cubic Ia3d mesoporous carbons containing nitrogen as much as 13%. The car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The loss of specific capacitance of the sym-GFAC-800 SC at higher current density may be explained by its high internal resistance, which causes a significant IR drop of 0.23 V at 10 A g −1 . 49 The IR drops observed for the sym-GFAC-800 SC during the GCD studies are comparable to the reported literature. 25,47,50 The energy density of the sym-GFAC-800 SC is compared with recent aqueous carbon-based high voltage SCs (Table SI).…”
Section: Resultssupporting
confidence: 87%
“…The loss of specific capacitance of the sym-GFAC-800 SC at higher current density may be explained by its high internal resistance, which causes a significant IR drop of 0.23 V at 10 A g −1 . 49 The IR drops observed for the sym-GFAC-800 SC during the GCD studies are comparable to the reported literature. 25,47,50 The energy density of the sym-GFAC-800 SC is compared with recent aqueous carbon-based high voltage SCs (Table SI).…”
Section: Resultssupporting
confidence: 87%
“…In addition, increasing the quantity of -N generally accelerates the active material's redox process. 46 The amount of N1s might have increased as a result of the strong π-π interaction between the PANI backbone and Cl-GO. 47,48 Furthermore, with the doping of Cl-GO, chlorine-containing oxygenated functional groups and higher electronegativity of chlorine atom compared to other heteroatoms (-S and -N), may have supported the formation of quinoid amine (=N-), secondary amine structure (-NH-) and positively charged nitrogen (-N+-) structures formed by polymerization reaction in PANI structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The original researches led by Ryoo developed a N-doped OMC for electric double layer capacitor (EDLC) electrodes in 2008. 124 In the pioneering studies, the SSA of N-doped OMC and the corresponding specific capacitance were not perfect. 124,125 The largest SSA of N-doped OMC by Ryoo and Kim et al were only 778 and 725 m 2 g −1 , respectively.…”
Section: Applications As Electrodes In Supercapacitorsmentioning
confidence: 99%
“… 124 In the pioneering studies, the SSA of N-doped OMC and the corresponding specific capacitance were not perfect. 124,125 The largest SSA of N-doped OMC by Ryoo and Kim et al were only 778 and 725 m 2 g −1 , respectively. The highest capacitance of the electrodes was 182 F g −1 at 10 mV s −1 , which was higher than that of pure OMC (147 F g −1 ).…”
Section: Applications As Electrodes In Supercapacitorsmentioning
confidence: 99%